TRANSLATION TECHNIQUE IN PITTACUS LORE’S NOVEL “I AM NUMBER FOUR” - Fernando De Napoli Marpaung; Yusrah; Adinda Nur Afriska (The Seall Journal, 2020)
In this study writer focus in translation technique and the most technique that be used translator in translating “I am Number Four “novel. In technique translators have a lot of different things to consider before diving into to translating a text. This study conducts on the descriptive qualitative method. Descriptive design simply describes what data shows. In order to account for this, translators use a wide variety of translation techniques in order to accurately translate any given text. Based on the data analysis which is taken from the novel ‘I Am Number Four’ written by Pittacus Lore in 2011 on chapter 3 page 13-14 and in Indonesian version, the novel is translated by Nur Aini in 2012 on chapter 3 page 24-26 . I Am Number Four was a young adult science fiction novel by Pittacus Lore. Pittacus lore was the pseudonym used by two of the authors, James Frey and the Jobie hughes. The writer finding the dominant technique that be used by the translator are literal and modulation technique. In 47 sentences the translator just use three times to pure borrowing technique and three times to deletion technique with the presentage literal translation (65,7%), modulation (25,7%), pure borrowing (4.3%), deletion (4,3%) . So literal and modulation technique are the most dominat used by Translator.